AB1205 Precision of serum and plasma testing in anti-cardiolipin and anti-Β2 glycoprotein-1 antibodies. (12th June 2018) - Pham, M.M.; Orsolini, G.; Crowson, C.S.; Snyder, M.R.; Pruthi, R.K.; Moder, K.G.
Abstract : Background: Anti-cardiolipin (aCL) and anti-β2 glycoprotein-1 (β2GP1) antibody ELISA testing may be performed on serum, plasma, or both in accordance to the manufacturers' suggested protocols. There exists some variability in manufacturers' preference for serum or plasma. Various societal guidelines have published a preference for serum over plasma; however, there is scarcity of data assessing reproducibility between serum and plasma in aCL or β2GP1 testing. Objectives: To determine reproducibility of aCL and β2GP1 testing between serum and plasma samples obtained in a routine clinical setting. Methods: Patients with clinical serum draws for IgG/IgM aCL and β2GP1 antibodies were identified, and same-day, citrated plasma samples were obtained for repeat ELISA testing (QUANTA Lite, INOVA Diagnostics, San Diego, CA). Quantitative levels were determined for each isotype and further stratified into Negative (<15.0 GPL/MPL or U/mL), Weakly Positive (15.0–39.9 GPL/MPL or U/mL), or Positive (≥40.0 GPL/MPL or U/mL) reference categories. Differences were compared using paired t-tests. Agreement between the reference categories were compared by kappa coefficients. Results: Fifty patients were identified for study with 50 and 40 samples eligible for repeat aCL and β2GP1 plasma testing, respectively. Mean age was 49±18 years. 70% were female, 86% were Caucasian, 22% with systemic lupus erythematosus and 22% with antiphospholipid syndrome. As shown in Table 1, quantitative levels tended to be slightly higher in serum than plasma. Although a statistically significant difference was found for most of the antibodies tested, the difference between serum and plasma values were generally small. There was good agreement in reference category between serum and plasma. Kappa coefficients ranged from 0.70 to 1.00. Conclusions: There appears good reproducibility of IgG/IgM aCL and β2GP1 antibody ELISA results between serum and plasma. References: [1] Lakos G, Favaloro EJ, Pierangeli SS, et al. Arthritis & Rheumatology. 2012 Jan 1;64(1):1–0. [2] Lewis DA, Pound ML, Ortel TL. Journal of Thrombosis and Haemostasis. 2006Jan 1;4(1):265–7. [3] Wong RC, Favaloro EJ, Mallon D, et al. Pathology. 2008Jan 1;40(1):58–63. [4] Wong RC, Gillis D, Sturgess A, et al. Pathology. 2004Feb 1;36(1):63–8. Acknowledgements: Special thanks to Susan Hartzler, Cory Blixt, Serena Navitskas, and Diane Meier. Disclosure of Interest: None declared